Assessing the Environmental Policy of a Natural Protected Area Using Visitor Opinions. Case Study of Parnassos National Park, Greece - MARTINIS, Aristotelis (Journal of Environmental Management and Tourism; Vol 11 No 3 (2020): JEMT Volume XI Issue 3(43) Summer 2020DO - 10.14505//jemt.v11.3(43).01, 2020)
Protected Areas (PAs) represent attractive destinations for visitors that seek contact with the natural environment, biodiversity, and cultural heritages. To manage PAs holistically ( i.e ., maintenance, protection, and sustainable development), managers must know the socio-economic and demographic characteristics of visitors. Here, questionnaire responses were used to investigate the profile, environmental perception, knowledge, and behaviour of two categories of visitors in the Parnassos National Park (Greece): summer visitors and winter visitors. Based on the questionnaires, compared to winter respondents (WR), summer respondents (SR) had a higher level of education, environmental knowledge, and environmental awareness. Most visitors (SR and WR combined) stated that they were willing to contribute financially to the protection, conservation of biodiversity, and maintenance of infrastructure in this PA. Based on our results, managers should place focus on attracting more summer visitors when shaping the future environmental policy of this PA. Examples of potential sustainable activities for summer visitors include educational trails, hiking trails, and climbing routes that incorporate the operation of ski lifts (for scenic rides up and walks down), as well as environmental activities drawing on local culture.